The Effect of National-Legal Culture on the Development of Tax Instruments in the National Legislation (International Journal of Psychosocial Rehabilitation, 2020)
The article examines present-day problems of interaction between taxpayers and the state, arising due to making different public legal payments. However, any interaction should be related to certain principles, which national tax policy can formulate. The tax policy, in its turn, should be based upon mainstream culture, and tax culture as well. The term “tax culture” constitutes an innovation in legal science, which, in conditions of the contemporary society, requires new approaches to consideration and detailed elaboration, what made the research subject matter relevant. The experience of the countries with effective and stable economies has been thoroughly analysed. The authors have made an attempt to identify the major instruments and mechanisms of effective economy in terms of forming tax policy of the countries, they have chosen as the subject of the research study. The article aims to identify, systematise, and analyse the universal instruments developed within the national tax policy, and which can be utilised when there is any form of the state structure and any form of government. A method of social questionnaire survey has revealed the specific features and patterns in tax culture of the people of different nationalities, what, in its turn, enabled understanding the specifics of the national tax policy formed in one or another state. A comparative legal research method and comparativistics method allowed to compare not only forms and types of societies, but legal systems, legislation, characterise and analyse by comparison, in particular, tax compliance, tax culture, and, hence, tax policy in foreign countries. The resulting data were obtained, which enable borrowing tax instruments developed in the European and American practice. An essential result of the study involves identification of a congruence effect, i.e. an adequate response of the state (provision of social benefits to taxpayers, in the scope appropriate to their taxation burden) to a citizen’s paying its tax liability. Hence, tax policy developed in the state has a direct effect on forming tax behaviour and, consequently, tax culture of people. Tax policies of the considered foreign countries, retaining their national identity, have succeeded in devising individual methods of relationships with taxpayers, within which they are partners to attain a common goal of accomplishing primary objectives of the state.